2020
DOI: 10.2196/17249
|View full text |Cite
|
Sign up to set email alerts
|

Guideline Recommendations for Oral Care After Acquired Brain Injury: Protocol for a Systematic Review

Abstract: Background Oral care is important to prevent buccal and systemic infections after an acquired brain injury (ABI). Despite recent advancements in the development of ABI clinical practice guidelines, recommendations for specific clinical processes and actions to attain adequate oral care often lack information. Objective This systematic r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Oral hygiene is often neglected due to a patients’ physical or cognitive difficulties. In this way, patients are reliant on nursing staff and caregivers to maintain their good oral hygiene [ 15 ]. Oral care could be improved with more training opportunities for nursing staff and caregivers, assessing patients’ remaining abilities on admission, and using protocols to guide proper oral care [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oral hygiene is often neglected due to a patients’ physical or cognitive difficulties. In this way, patients are reliant on nursing staff and caregivers to maintain their good oral hygiene [ 15 ]. Oral care could be improved with more training opportunities for nursing staff and caregivers, assessing patients’ remaining abilities on admission, and using protocols to guide proper oral care [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, dental caries and periodontal diseases can be seen (2). Stroke patients, who cannot perform their self -care because of their physical and/or cognitive status, are dependent on their nurses or caregivers (17). Some previous studies have shown that more than two -thirds of the patients had difficulty in brushing teeth in a way in relation to the severity of stroke.…”
Section: Oral Health Problems In Stroke Patientsmentioning
confidence: 99%